2014
DOI: 10.1021/ja4114374
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Bilayer Lipid Composition on the Structure and Topology of the Transmembrane Amyloid Precursor C99 Protein

Abstract: C99 (also known as β-CTF) is the 99 residue transmembrane C-terminal domain (residues 672–770) of the amyloid precursor protein and is the immediate precursor of the amyloid-β (Aβ) polypeptides. To test the dependence of the C99 structure on the composition of the host model membranes, NMR studies of C99 were conducted both in anionic lyso-myristoylphosphatidylglycerol (LMPG) micelles and in a series of five zwitterionic bicelle compositions involving phosphatidylcholine and sphingomyelin in which the acyl cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
82
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(85 citation statements)
references
References 32 publications
3
82
0
Order By: Relevance
“…Bicelles have been employed to study a variety of membrane-associated proteins in their active forms [6972]. Vlach and Saad showed that titration of HIV-1 MA with 1,2-dihexanoyl- sn -glycero-3-phosphocholine (DHPC) micelles and DMPC/DHPC bicelles caused NMR chemical shift perturbations consistent with membrane-promoted exposure of the myristoyl group [61].…”
Section: Resultsmentioning
confidence: 99%
“…Bicelles have been employed to study a variety of membrane-associated proteins in their active forms [6972]. Vlach and Saad showed that titration of HIV-1 MA with 1,2-dihexanoyl- sn -glycero-3-phosphocholine (DHPC) micelles and DMPC/DHPC bicelles caused NMR chemical shift perturbations consistent with membrane-promoted exposure of the myristoyl group [61].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, structures of C99 1−99 monomer peptide in LMPG micelles and in a series of five zwitterionic bicelle compositions (phosphatidylcholine and sphingomyelin where the acyl chain lengths varied from 14 to 24 carbons) suggest that the helicity of the TM domain of C99 is relatively insensitive to membrane lipid composition (22,28). These contrasting conclusions for the structures of both the monomers and dimers raise important questions related to the role of environment in modulating C99 monomer structure and C99 homodimer structure and stability.…”
mentioning
confidence: 99%
“…This 418 might be related to the processive cleavage by the γ-secretase, as flexi-419 bility allows the helix to adopt to the sluice-like active site of the prote-420 ase[146][147][148][149]. Importantly, the proteolytic efficiency is enhanced 2-4 421 fold in the presence of cholesterol[150].422In recent studies a cholesterol-binding site and a homodimerization 423 interface at C99 were defined[146,[151][152][153]. Homodimerization and 424 cholesterol binding were found to compete, as both involve the glycine 425 zipper motif G 700 xxxG 704 xxxG 708 G 709[151] (Fig.…”
mentioning
confidence: 99%